ENGAGED AND COMMITTED IN THE HYBRID ERA: PATHWAYS TO EMPLOYEE PERFORMANCE - Zhafira, Nabila Hilmy; Makmun, Abu Hassan; Yusnaidi, Yusnaidi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
The COVID-19 pandemic has accelerated the transition to hybrid work, encouraging adaptability and efficiency across a range of generational groups. This study proposes a conceptual framework to examine the complex relationship between hybrid work arrangements, employee engagement, commitment, and performance among Indonesian Gen Z and Millennials. This study posits that hybrid work arrangements promote work-life balance and productivity but may lower performance due to social isolation and lower work engagement. The model highlights the dual-edge nature of this work model and the necessity of efficient HR policies to improve performance and retention in hybrid settings.